Efisiensi Pemasaran Sayur-Mayur di Desa Pombulaa Jaya Kecamatan Konda Kabupaten Konawe Selatan - Nuriyani, Nuriyani; Bafadal, Azhar; Indarsyih, Yusna (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2018)
This study aimed to determine the pattern of marketing channels, how much cost, profit, and marketing margin and to know the efficiency of marketing vegetables (long beans, spinach, and kale). This research was conducted in November 2016 until October 2017 in Pombulaa Jaya Village KondaSubdistrict of South Konawe Regency. The population of this research was all farmers of vegetables in Pombulaa Jaya Village amount 50 farmers. The sample used in this research is vegetable farmer and vegetable marketing agency. Based on the research result, the number of selected sample farmers was 37 vegetable farmers. While, the number of sample traders in this study were 7 traders consisted of 2 merchant collectors and 5 retailers. The results showed that invegetables marketing there were two patterns of marketing channels that used was marketing channel I consists of farmers → collector traders → retailers → consumer and marketing channel II was farmers → retailers → consumer. The marketing cost for marketing of I for long beans was Rp 937,500 per month, spinach Rp 793,200 per month, and kangkung Rp 1,689,300 per month and marketing channel II cost for bean length Rp 420,000 per month, spinach Rp 210,000 per month, and kale of 210,000 per month. The marketing advantage of marketing channel I for long beans was Rp 12,112,500 per month, spinach Rp 8,206,800 per month and kangkung Rp 15,560,700 per month and marketing channel II for bean length Rp 2,580,000 per month, spinach for Rp 1.290.000 per month and kangkung Rp 1.290.000 per month. Marketing margin on marketing channel I for peanuts was Rp 7.500 per kg, spinach Rp 6,000 per kg and kangkung Rp 7,000 per kg, while marketing channel II for bean length Rp 2,000 per kg, spinach Rp 2,000 and kangkung Rp 2,000 per kg. In termseconomic, the marketing channel II in Pombulaa Jaya Village was the most efficient compared to marketing channel I because it has the lowest percentage of marketing margin that was 40% long beans, 50%.